Meerkat: Scalable Replicated Transactions Following the Zero-Coordination Principle - Szekeres, Adriana; Whittaker, Michael; Sharma, Naveen Kr.; Li, Jialin; Krishnamurthy, Arvind; Ports, Dan R. K.; Zhang, Irene (Eurosys 2020, 2020)
Traditionally, the high cost of network communication between servers has hidden the impact of cross-core coordination in replicated systems. However, new technologies, like kernel-bypass networking and faster network links, have exposed hidden bottlenecks in distributed systems.This paper explores how to build multicore-scalable, replicated storage systems. We introduce a new guideline for their design, called the Zero-Coordination Principle. We use this principle to design a new multicore-scalable, in-memory, replicated, key-value store, called Meerkat. Unlike existing systems, Meerkat eliminates all cross-core and cross-replica coordination, both of which pose a scalability bottleneck. Our experiments found that Meerkat is able to scale up to 80 hyper-threads and execute 8.3 million transactions per second. Meerkat represents an improvement of 12x on state-of-the art, fault-tolerant, in-memory, transactional storage systems built using leader-based replication and a shared transaction log.